Sosialisasi Permainan Tradisoinal Bagi Anak Desa Pasar Bantal Kabupaten Muko-Muko - Putra, Yudi Pramana; Perdima, Feby Elra; Sumantri, Ajis (Jurnal Kewirausahaan & Inovasi, 2024)
The socialization of traditional games plays a crucial role in children's development. These games not only provide a means of entertainment, but also play an integral role in the development of various aspects of a child's well-being. Through direct interaction, traditional games help children develop social skills such as communication, cooperation and understanding of shared rules. In addition, these games also support the development of gross and fine motor skills through the physical movements involved. Aspects of creativity and imagination are also enhanced, while cultural values and traditional heritage are applied and valued. Traditional games provide a platform for cognitive learning, involving problem solving and improved concentration. The child's social and emotional experience is enriched through the acceptance of victory and failure with sportsmanship. In addition, these games have a positive impact on children's mental and physical health by providing enjoyable physical activity and reducing stress. In the context of globalization and modern lifestyle changes, the preservation and promotion of traditional games is becoming increasingly important as an effort to ensure children remain connected to their cultural heritage. Therefore, initiatives to introduce children to traditional games not only provide entertainment, but also form a solid foundation for their holistic growth and development.